STRATEGI PEMBANGUNAN PERIKANAN BUDIDAYA DI KABUPATEN KAMPAR PROVINSI RIAU - Yusrizal Yusrizal; Darwis Darwis; Zulkarnain Umar (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
The purpose of this research is to analyze the implementation of fishery aquaculture development program, synergy development of aquaculture culture and to describe strategy of synergy of development of aquaculture fishery in Kampar regency. The research method used is field survey method with interview and questionnaire. The results showed that the implementation of the development of aquaculture reached 55.89% of the realization of the budget of Rp 57.595 billion, with the activity of 11 (eleven) activities / projects, in synergy fisheries development there are two aspects that must be synergized, management aspects (planning, organizing, controlling) and aspects of human resources, (regulation, budgeting, aperature resources), SWOT analysis shows that Kampar Regency has some power to exploit the big opportunities, for the strategy of synerginity of aquaculture development in the first quadrant (one) the government can utilize SO (Strengths-Opportunities).